METODE MONITORING DAN EVALUASI : DISKUSI - Nabiu, Musryadi; Sukiyono, Ketut (Jurnal AGRISEP, 2004)
This paper was aimed at discussing a quantitative method  for monitoring  and evaluation  (monev) indevelopment  projects.   The first  part,  a  current  concept  and  method  of  monev  will  be  reviewed followed  by discussion  on monev  process  focussing  on the  application  of monev  on project  and sectoral level